DARI QAWĀ‘ID KE KOMUNIKATIF: TRANSFORMASI METODE PEMBELAJARAN BAHASA ARAB - Muhammad Ivang Rizaldi; Shifany Maulida Hijjah (Tarbawi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
Arabic language instruction faces a methodological tension between traditional structure-based approaches and modern function-based communicative approaches. This study aims to describe the characteristics of traditional and modern Arabic teaching methods, compare their pedagogical orientations, and explain the influence of each method in contemporary Arabic instruction. This research employs a qualitative methodology with a library research design, analyzing primary sources from reference books and scholarly articles that discuss Arabic language teaching. The findings reveal that traditional methods such as qawā'id wa al-tarjamah, sorogan, bandongan, and rote memorization position language as a system of knowledge mastered through grammatical structure, textual authority, and intellectual discipline. In contrast, modern methods including the direct method, audio-lingual method, communicative language teaching, and eclectic method view language as a tool for social interaction developed through active communicative practice, the teacher's role as a facilitator, and evaluation based on fluency and function. The comparison of pedagogical orientations confirms a fundamental epistemological difference, yet in current educational practice both approaches are no longer dichotomous as various institutions begin to integrate nahwu sharaf techniques into communicative contexts. The implication of these findings is the emergence of methodological flexibility that enables teachers to adjust strategies based on institutional goals and learner characteristics. Arabic language education institutions are advised to develop reflective methodology training programs for educators, encourage applied research on the effectiveness of method combinations, and strengthen epistemological literacy among students of Arabic language education programs.